Management Accounting - A. Atkinson Anthony (Pearson Prentice Hall, 2004)
"The principles contained in this book are relevant to us on a daily basis as we make decisions that impact the sales and profits of the Butterfinger candy bar franchise. We use the tools to evaluate media spending, to determine the extent to which we customize product offerings for retailers, to determine when to increase/decrease number of SKUs in the franchise, to identify significant consumer complaints with the product so as to determine corrective action, etc. This is a must read for anyone interested in growing a business." – Anne Loveland, Associate Marketing Manager, Nestle USA